Theory of Square-Wave Voltammetry of Two-Electron Reduction with the Adsorption of Intermediate - Milivoj Lovric; Šebojka Komorsky-Lovric (International Journal of Electrochemistry)
Thermodynamically unstable intermediate of fast and reversible two-electron electrode reaction can be stabilized by the adsorption to the electrode surface. In square-wave voltammetry of this reaction mechanism, the split response may appear if the electrode surface is not completely covered by the adsorbed intermediate. The dependence of the difference between the net peak potentials of the prepeak and postpeak on the square-wave frequency is analyzed theoretically. This relationship can be used for the estimation of adsorption constant.